FRI0397 THE IMPACT OF OSTEOARTHRITIS DISEASE SEVERITY ON HEALTHCARE RESOURCE USE: ANALYSIS OF REAL-WORLD EUROPEAN DATA. (13th June 2020) - Conaghan, P. G.; Abraham, L.; Graham-Clarke, P.; Viktrup, L.; Cappelleri, J. C.; Beck, C.; Bushmakin, A. G.; Hatchell, N.; Clayton, E.; Jackson, J.
Abstract : Background: Osteoarthritis (OA) is a chronic joint disease associated with pain and impaired activity. With increasing obesity trends and an ageing population, the prevalence of OA is expected to rise in the future. This represents an increasing societal problem which will lead to an increased burden on healthcare services. Objectives: To understand the pattern of healthcare resource utilisation (HCRU) across France, Germany, Italy, Spain and the UK, as OA disease severity increases. Methods: Data were drawn from the Adelphi OA Disease Specific Programme (2017-18), a point-in-time study of physicians and their OA patients. OA disease severity was reported by physicians, who categorised patients' OA severity as mild, moderate or severe. Patients were excluded from the analyses if they suffered from back and neck OA only, and shoulder OA that had not been diagnosed by X-ray. Physicians provided information, on a patient record form, about OA-related visits to healthcare professionals (HCPs), tests/scans conducted, emergency room (ER) visits and surgeries. Statistical comparisons among disease severity groups were made by analysis of variance and chi-squared tests. Results: The study included 489 physicians (primary care physicians, rheumatologists, orthopaedists) reporting on 3596 of their patients with OA: 24% mild (n=874), 53% moderate (n=1904) and 23% severe (n=818). Over the last 12 months, the mean number of consultations with HCPs increased with disease severity (3.7 mild, 4.2 moderate and 5.7 severe [<0.001]). This pattern was also observed in relation to the mean number of tests/scans conducted in the last 12 months (6.9 mild, 7.9 moderate and 9.3 severe [<0.001]). More than a quarter of severe patients visited the ER in the last 12 months (26% vs. 4% mild; 9% moderate [<0.001]) and visits to hospital increased with disease severity (Table 1 ). The proportion of patients that have had a surgery due to their OA rose with worsening disease severity (11%, 13% and 27% for mild, moderate and severe, respectively [<0.001]). Conclusion: This real-world data demonstrated an increase in visits to HCPs, monitoring tests and scans, hospitalisations, ER visits and surgery as OA disease severity worsened. Disclosure of Interests: Philip G Conaghan Consultant of: AbbVie, BMS, Eli Lilly, EMD Serono, Flexion Therapeutics, Galapagos, GSK, Novartis, Pfizer, Speakers bureau: AbbVie, Eli Lilly, Novartis, Pfizer, Lucy Abraham Shareholder of: Pfizer, Employee of: Pfizer, Peita Graham-Clarke Shareholder of: Eli Lilly and Co, Employee of: Eli Lilly and Co, Lars Viktrup Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Joseph C Cappelleri Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Craig Beck Shareholder of: Pfizer, Employee of: Pfizer, Andrew G Bushmakin Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Niall Hatchell: None declared, Emily Clayton: None declared, James Jackson: None declared